Phosphatidylinositol 3-kinase binds to alpha-actinin through the p85 subunit. - Shibasaki, F (1994)
Phosphatidylinositol 3-kinase (PI 3-kinase) has been shown to play an important role in the signal transduction of cell growth. It is also suggested that it is involved in cytoskeletal reorganization. We have found that alpha-actinin copurifies with PI 3-kinase from bovine thymus. The antibody against PI 3-kinase 85 kDa subunit (p85) also co-immunoprecipitates alpha-actinin from lysates of NIH/3T3 cells. In addition, anti-alpha-actinin antibody coprecipitates PI 3-kinase activity. This coprecipitation was observed even after depolymerization of actin fibres, suggesting that PI 3-kinase binds directly to alpha-actinin. As alpha-actinin is a phosphatidylinositol 4,5-bisphosphate (PI4,5P2)-binding protein, binding experiments using various constructs of truncated p85 were carried out in the presence or absence of PI4,5P2. In the absence of PI4,5P2, chicken gizzard alpha-actinin binds only to the whole p85 construct, but it binds to the proline-rich region of p85 fragments in the presence of PI4,5P2. This binding is enhanced with increased concentrations of Pi4,5P2 up to 10 microM, whereas phosphatidylinositol and phosphatidylinositol 4-phosphate were not good activators of alpha-actinin binding. These results suggest that PI 3-kinase binds to alpha-actinin and regulates cytoskeletal reorganization.